(untitled) (Revista de Crítica Literaria Latinoamericana, 2016)
Despite the distinction of having Rubén Darío as its literary editor, the fashion magazine Elegancias (1911-1914) has received little attention from critics. The current essay offers the first rigorous examination of the magazine’s full archives. The first part focuses on clarifying Darío’s involvement with the magazine as well as the details of its publication. The second part centers on Dario’s representation of the learned woman in his articles in Elegancias, with a special emphasis on four texts that have not been reproduced since their original appearance in Elegancias: the reviews “Greta Prozor,” “Dos artistas argentinas,” “Mimí Aguglia,” and “Delfina Bunge de Gálvez.” Finally, an appendix offers a detailed list of Darío’s contributions to Elegancias, including some philological notes. This study is part of a larger project examining Elegancias as a text that illuminates the little-explored relationship of Spanish American Modernism with its female readership, particularly modernistas’ use of the language of fashion in an effort to both please and mold these readers in light of the “dangerous fashions” of feminism and suffragism.